Una nueva variedad de anopheles pseudopunctipennis (1948)
A new variety of Anopheles pseudopunctipennis from Florida, Valle, Colombia (1006 m. above sea level), near Cali, is described. A comparative diagnosis is made between egg, larva and hypopygium of willardi, typicus and bifoliata n. var. The possible hybridization between bifoliata and typicus, is noted.